Effect of the phosphate solubilization and mineralization synergistic mechanism of Ochrobactrum sp. on the remediation of lead - Jiang, Yi; Zhao, Xingqing; Zhou, Yucheng; Ding, Congcong (Environmental science and pollution research international, 2022)
Phosphate-solubilizing bacteria (PSB) promotes the formation of mineralized precipitation through phosphorous dissolution and mineralization, forming stable lead (Pb(II)) minerals and reducing the migration of Pb(II) in the environment. In this study, a Pb-tolerant strain Ochrobactrum sp. J023 from a contaminated soil around a battery factory in Jiangsu Province, China, was screened for experiments to investigate the phosphate solubilization and mineralization mechanism of this strain. The organic acids and the acid phosphatase produced by the bacteria have a synergistic effect on phosphate dissolution. When the pH of the culture medium decreased to the lowest 4.55, the amount of soluble phosphate and the activity of acid phosphatase reached the maximum 161.29 mg L −1 and 61.98 U mL −1 , and there was a significant correlation between the concentration of soluble phosphate and the activity of acid phosphatase ( R = 0.832**, P < 0.05). It was found that acetic acid played the most important role in the secreted organic acids. During the mineralization reaction, the extracellular polymeric substances (EPS) chelates part of the Pb(II) on the surface of the cell wall, preventing the metal Pb from penetrating into the cell, thus providing protection to the strain. Meanwhile, due to the nucleation sites provided by cell surface groups (carboxyl and phosphate groups), a large number of metal ions are absorbed to promote the formation of crystallization. The final mineralized product of Pb(II) by strain J023 was pyroxite (Pb 5 (PO 4 ) 3 X, where X = Cl, OH). The mechanism of phosphate dissolution and mineralization proposed by us is that the organic acids and acid phosphatases secreted by phosphate-solubilizing bacteria promote the increase of PO 4 3− concentration in the solution, the complexation of metal cations and cell surface groups will induce the formation of mineralized precipitation under the catalysis of enzyme. Therefore, it is a promising strategy for bioremediation of lead pollution by screening functional strains with strong abilities of phosphate solubility and mineralization.